A Study of Maternal Outcome of Booked and Unbooked Cases - Sanobar Baloch, Sajida Munir Siddique, Nahil Shams, Kanta Bai Ahuja, Rozina Mujeeb Sahito, Mir Mehrab Jan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The provision of antenatal services is a matter of great importance because it not only enables women to receive appropriate healthcare, but it also ensures that any issues that may arise during childbirth are detected and managed effectively through timely consultations with specialists. Aim: The aim is to ascertain how often booked cases appear during childbirth and to contrast the outcomes for mothers in the local population who have pre-booked appointments with those who have not. Methods: A observational study was carried out for six months at Indus Medical Collage Tando Muhammad Khan, Pakistan. Non-probability consecutive sampling was used to select participants. Participants were asked to provide informed consent and were asked about their demographic information and obstetric history. The cases were classified as either "booked" or "un-booked" based on an operational definition, and their maternal outcomes were recorded in relation to delivery. Results: Pre-eclampsia, out of a total of 180 participants, 42 (23.33%) were diagnosed with the condition. Of those 42 cases, 18 occurred in the booked group and 24 in the unbooked group. preeclampsia, 8.33% of unbooked women from low SES groups had preeclampsia, compared to only 5.0% of unbooked women from middle SES groups (p-value = 0.003). Similarly, for preterm birth, 10.55% of unbooked women from low SES groups had preterm births, compared to only 2.77% of unbooked women from middle SES groups (p-value < 0.0001). Conclusion: The findings of our research indicated that most individuals who encountered unfavorable maternal consequences, such as surgical delivery, gestational hypertension, and premature delivery, belonged to the unregistered category. Conversely, the registered group demonstrated significantly lower occurrences of these complexities. Keywords: booked and unbooked, pregnancy complications, Preeclampsia, maternal outcome